The relevance of health education in controlling and preventing Ascaris lumbricoides infection in children - D’Alessandro, Aline Almeida Barbaresco; D’Alessandro, Walmirton Bezerra; Herrera, Sávia Denise Silva Carlotto; Mendes, Seyna Ueno Rabelo; Paiva, Maykon Jhuly Martins de; Holanda, Francisco de Sousa; Azevedo, David Salen Alves; Bueno, Luana Mendonça Marques Ramos; Pedreira, Layra Eugenio; Campelo, Gabriella Silva Costa (Seven Editora, 2023)
Ascariasis is an intestinal parasitic infection caused by Ascaris lumbricoides. Although it is found globally, this disease is more prevalent in developing countries, such as Brazil, due to the lack of infrastructure and basic sanitation. The deficiency in Public Health services in these regions favors the spread of the parasite, especially among the economically disadvantaged population living in precarious conditions, affecting mainly children. The objective of this study was to conduct a detailed review of the importance of health education in controlling and preventing ascariasis in childhood. Using an indirect approach, searches were carried out in various databases available on virtual platforms. The results pointed to insufficient knowledge among the majority of the Brazilian population regarding the modes of transmission and prevention of this disease, contributing to high prevalence rates of this parasitic infection. Therefore, it is believed that the dissemination of more comprehensive knowledge and information about ascariasis is key to preventing this illness. Health education emerges as a crucial strategy to instruct the population, especially parents and caregivers, on hygiene practices and preventive measures. Investing in educational programs targeted at vulnerable communities can play a fundamental role in reducing the spread of the parasite and promoting healthy habits, resulting in a significant impact on the prevention and control of ascariasis, especially among children. DOI:https://doi.org/10.56238/innovhealthknow-059